Association between maternal periconceptional alcohol consumption and neural tube defects: Findings from the National Birth Defects Prevention Study, 1997–2011. Issue 5 (27th February 2020) - Louden, Adia R.; Suhl, Jonathan; Kancherla, Vijaya; Caspers Conway, Kristin M.; Makelarski, Jennifer; Howley, Meredith M.; Hoyt, Adrienne T.; Olney, Richard S.; Olshan, Andrew F.; Romitti, Paul A.
Abstract: Background: Neural tube defects (NTD)s are common birth defects with a multifactorial etiology. Findings from human studies examining environmental (non‐inherited) exposures tend to be inconclusive. In particular, although animal studies of alcohol exposure and NTDs support its teratogenic potential, human studies are equivocal. Using data from the National Birth Defects Prevention Study (NBDPS), associations between maternal periconceptional (1 month before through 1 month after conception) alcohol consumption and NTDs in offspring were examined. Methods: NTD cases and unaffected live born singleton controls with expected dates of delivery from October 1997–December 2011 were enrolled in the NBDPS. Interview reports of alcohol consumption (quantity, frequency, variability, type) from 1, 922 case and 11, 251 control mothers were analyzed. Crude and adjusted odds ratios (aOR)s and 95% confidence intervals (CI)s for alcohol consumption and all NTDs combined and selected subtypes (spina bifida, anencephaly, encephalocele) were estimated using unconditional logistic regression analysis. Results: Among mothers in the NBDPS, 28% of NTD case and 35% of control mothers reported any periconceptional alcohol consumption. For each measure of alcohol consumption, inverse associations were observed for all NTDs combined (aORs = 0.6–1.0). Results for NTD subtypes tended to be similar, but CIs for spina bifida and encephalocele were more likely to include the null. Conclusions: These findings suggest a lack of positive associations between maternal periconceptional alcohol consumption and NTDs. Future studies should continue to evaluate the association between maternal alcohol consumption and NTDs in offspring accounting for methodological limitations such as potential misclassification from self‐reported alcohol consumption.